The Measurement of The Volatility of Market Risk of Viet Nam Insurance Industry After The Low Inflation Period 2015-2017 - Huy, Dinh Tran Ngoc (IJRDO - Journal of Business Management, 2019)
This paper measures the volatility of market risk in Viet Nam insurance industry after this period (2015-2017). The main reason is the necessary role of the insurance company system in Vietnam in the economic development and growth in recent years always go with risk potential and risk control policies. This research paper aims to figure out how much increase or decrease in the market risk of Vietnam insurance firms during the post-low inflation environment 2015-2017. First, by using quantitative combined with comparative data analysis method, we find out the risk level measured by equity beta mean in the insurance industry is acceptable, as it is little lower than (<) 1. Then, one of its major findings is the comparison between risk level of insurance industry during the financial crisis 2007-2009 compared to those in the post-low inflation time 2015-2017. In fact, the research findings show us market risk level during the post-low inflation time has increased much. Finally, this paper provides some ideas that could provide companies and government more evidence in establishing their policies in governance. This is the complex task but the research results shows us warning that the market risk might be higher during the post-low inflation period 2015-2017. And our conclusion part will recommends some policies and plans to deal with it.